Interactive Electronic Module: Is It Beneficial for Learning? - Rahmiati; Saputra, Indra; Oktarina, Rahmi (Journal for Lesson and Learning Studies, 2023)
Low motivation and student learning outcomes in research methodology courses. E-modules can greatly increase student motivation and learning outcomes in research methodology courses. This study aimed to increase the motivation and learning outcomes of cosmetology and beauty students in research methodology courses by implementing interactive electronic modules. This research is quasi-experimental with a pretest-posttest control group design with research subject students in research methodology courses. Data was collected using instruments like closed questionnaires, open questionnaires and tests. The data analysis used was quantitative descriptive analysis, discriminating power analysis using the T-test and qualitative descriptive analysis. The results of this study illustrate an increase in student motivation by 10.17% in the experimental class using the interactive e-module, while the control class using the printed module only increased by 2.08%. The results of the t-test showed that there was a significant difference in the experimental class, while the Sig (2-tailed) value in the control class proved that there was no difference. The e-module is proven to increase student motivation and learning outcomes significantly, and the module can be used to learn research methodology.